Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1155/2013/210686
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Targeted Therapies in Metastatic Castration-Resistant Prostate Cancer: Evolving Paradigms

Abstract: Majority of patients with metastatic castrate resistant prostate cancer (mCRPC) develop bone metastases which results in significant morbidity and mortality as a result of skeletal-related events (SREs). Several bone-targeted agents are either in clinical use or in development for prevention of SREs. Bisphosphonates were the first class of drugs investigated for prevention of SREs and zoledronic acid is the only bisphosphonate that is FDA-approved for this indication. Another bone-targeted agent is denosumab w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
14

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 69 publications
(79 reference statements)
0
24
0
14
Order By: Relevance
“…These associations are consistent with an interaction between abiraterone and BTT use that may benefit clinical outcomes. In fact there is accumulating preclinical and clinical evidence of a potential anticancer effect of bisphosphonates [13]. In a retrospective analysis of a phase 3 clinical trial on zoledronic acid versus placebo, zoledronic acid–mediated normalization of bone markers was associated with improved survival in men with bone metastases from CRPC [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These associations are consistent with an interaction between abiraterone and BTT use that may benefit clinical outcomes. In fact there is accumulating preclinical and clinical evidence of a potential anticancer effect of bisphosphonates [13]. In a retrospective analysis of a phase 3 clinical trial on zoledronic acid versus placebo, zoledronic acid–mediated normalization of bone markers was associated with improved survival in men with bone metastases from CRPC [28].…”
Section: Discussionmentioning
confidence: 99%
“…The BTT agents bisphosphonates and denosumab inhibit osteoclast-mediated bone resorption and can prevent bone loss and increase bone mineral density in patients with prostate cancer receiving androgen deprivation therapy [1012]. Zoledronic acid and denosumab are effective for the prevention of skeletal-related events in patients with metastatic prostate cancer [13]. Historically, bone-seeking radiopharmaceuticals have been used as a palliative treatment for pain in patients with metastatic prostate cancer [14].…”
Section: Introductionmentioning
confidence: 99%
“…35 This landmark study led to the US Food and Drug Administration approval of denosumab (commercialized as Prolia) in non-metastatic prostate cancer patients undergoing ADT as the only approved therapy to prevent hormone therapyassociated fractures. 36 Selective estrogen-receptor modulators Selective ER modulators (SERMs) have shown some promising results for BMD preservation in PCa for patients undergoing ADT. Raloxifene was first studied and was associated with an increase in BMD at the total hip and the trochanter (Po0.001) compared with placebo in a 12-month randomized trial of 48 men with non-metastatic PCa undergoing ADT.…”
Section: Denosumabmentioning
confidence: 99%
“…Data from these studies showed that there was no evidence of long-term toxicity during the 2-year follow-up and administered activities of at least 50 kBq/kg had a significant positive effect in bone alkaline phosphatase (ALP), prostate-specific antigen (PSA) levels, pain reduction and overall survival (El-Amm et al, 2013;Harrison et al, 2013;Nilsson et al, 2012). In general, 223 RaCl 2 was well tolerated, and no dose-limiting hemotoxicity was observed (Harrison et al, 2013).…”
Section: Iiii 223 Ra-chloridementioning
confidence: 99%